2019
DOI: 10.7771/2157-9288.1178
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Learning From an Authentic Engineering Context

Abstract: for additional information. This is an Open Access journal. This means that it uses a funding model that does not charge readers or their institutions for access. Readers may freely read, download, copy, distribute, print, search, or link to the full texts of articles. This journal is covered under the CC BY-NC-ND license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Additionally, we found that the 10 remaining studies relied on other forms of theoretically -grounded support to justify their design innovations. For example, some studies (Dasgupta, 2019;Fan et al, 2018;Langman et al, 2019;Moore et al, 2014;Tang, 2013;Weber et al, 2014) used educational goals and requirements described in standards and high-level reports, including those published by organizations such as the National Academies, National Research Council (e.g., Next Generation Science Standards), Council of Chief State School Officers (e.g., Common Core Standards) and the accreditation body for engineering programs (i.e., ABET). Other studies (Diefes-Dux et al, 2010;Guisasola et al, 2017;Yueh et al, 2014) relied on well-researched pedagogical frameworks (i.e., model-eliciting activities, teaching and learning sequences, and virtual laboratories) to support their design ideation.…”
Section: What Form Do the Findings Take?mentioning
confidence: 99%
“…Additionally, we found that the 10 remaining studies relied on other forms of theoretically -grounded support to justify their design innovations. For example, some studies (Dasgupta, 2019;Fan et al, 2018;Langman et al, 2019;Moore et al, 2014;Tang, 2013;Weber et al, 2014) used educational goals and requirements described in standards and high-level reports, including those published by organizations such as the National Academies, National Research Council (e.g., Next Generation Science Standards), Council of Chief State School Officers (e.g., Common Core Standards) and the accreditation body for engineering programs (i.e., ABET). Other studies (Diefes-Dux et al, 2010;Guisasola et al, 2017;Yueh et al, 2014) relied on well-researched pedagogical frameworks (i.e., model-eliciting activities, teaching and learning sequences, and virtual laboratories) to support their design ideation.…”
Section: What Form Do the Findings Take?mentioning
confidence: 99%
“…Progressive refinement means that design-based researchers report on variations and revisions as designs are improved. Along the way, they may also develop theory about education (e.g., Langman et al, 2019). For engineering knowledge, many concepts have not been studied at length so understanding and documenting students' development of knowledge needs to occur and tasks need to be designed to elicit that knowledge.…”
Section: Stages Of Design: Cycles and Iterationsmentioning
confidence: 99%
“…Of the studies examined in this systematic review, eight explored aspects of engineering education in K-12 settings (Blanchard, 2015;Dasgupta, 2019;Gale et al, 2019;Hardre et al, 2010;Hira & Hynes, 2019;Langman et al, 2019;Moore et al, 2014;Tang, 2013). Moore and colleagues (2014) sought to create a standards framework to inform quality K-12 engineering education.…”
Section: Synthesis Of Study Focusmentioning
confidence: 99%
See 2 more Smart Citations